'Going Out' or Staying In? The Expansion of Chinese NGOs in Africa. (May 2016) - Hsu, Jennifer Y.J.; Hildebrandt, Timothy; Hasmath, Reza
Abstract : This article examines the overseas behaviour of Chinese non‐governmental organisations (NGOs) in two African nations, Ethiopia and Malawi, with varying political regime types. Our findings suggest that, irrespective of regime type, Chinese NGOs have yet to make a substantial impact in either nation. We argue that, despite the strength of the Chinese state and high levels of international development assistance given, domestic politics and regulatory frameworks in host nations still matter a great deal. Our study suggests that the Chinese model of international development will continue to be one in which temporary one‐off projects are favoured; and, insofar as social organisations will play a role, they will be in the domain of government‐organised NGOs rather than grassroots NGOs.